Quality of Life Assessment of the Diabetic Patients Residing in Dehradun Using WHOQOL-BREF Scale - Khundia, Anshul; Kath, Khipenlo; Kala, Kanishk (Indian Journal of Pharmacy Practice)
Introduction: Diabetes Mellitus (DM) is a chronic disease characterized by high blood sugar, which not only affects the physical health of patients but also affects psychological, social, physical and environmental functioning. People with Diabetes (PWD) suffer from various problems that reduce their quality of life, which is still affected by frequent complications, the stigma of a chronic disease and various myths and misconceptions. Therefore, a careful assessment of physical health, treatment, treatment regimen and Quality of Life (QoL) is important to improve overall health. Aim: This study aimed to assess the Quality of Life (QoL) among adults with diabetes mellitus using the WHOQOL-BREF scale and to identify socio-demographic predictors influencing QoL. Materials and Methods: A cross-sectional study surveyed 394 adults aged 21 years and older diagnosed with diabetes in urban and semi-urban areas of Patel Nagar, Dehradun, Uttarakhand. Participants completed the WHOQOL-BREF questionnaire, evaluating four domains: physical health, psychological health, social relationships, and environment. Data were analyzed using describe statistics and domain-specific comparisons by age and gender. Results: The study found varying QoL scores across domains, with younger males generally reporting higher scores compared to older females. Socio-demographic factors such as age, gender, social habits, socio-economic status, and living conditions significantly influenced QoL outcomes. Conclusion: Enhancing QoL for diabetic patients necessitates comprehensive strategies that address socio-demographic disparities and domain-specific challenges. Gender-sensitive approaches are particularly crucial in optimizing care and support for individuals managing diabetes mellitus.
Keywords: Diabetes Mellitus; People with diabetes; Quality of life; WHO; WHOQOL